"Instant Happiness": Smartphones as tools for everyday emotion regulation. Issue 170 (February 2023) - Shi, Yaoxi; Koval, Peter; Kostakos, Vassilis; Goncalves, Jorge; Wadley, Greg
Highlights: We investigated smartphone-based emotion regulation in daily life and its associated psychological consequences using experience sampling and qualitative interviews. Smartphones are used to regulate boredom, stress, loneliness, tiredness, and sadness. Up to half of smartphone use may be for the purpose of emotion regulation. Users perceive smartphone-based emotion regulation to be effective in attaining desired emotional states; however the effect appears to be short-term. We contribute a novel method for studying digital emotion regulation. Abstract: Smartphone use has become an indispensable aspect of daily life for billions of people. Increasingly, researchers are examining the impact of smartphone use upon psychological well-being. However, little research has investigated how people deliberately use their smartphones to shape affective states; in other words, how smartphones are used as tools to support everyday emotion regulation. In this paper, we report a study that uses quantitative (experience sampling) and qualitative (semi-structured interview) methods to examine when and how people use smartphones to regulate emotions in everyday life, and the associated psychological consequences. Participants report spending a significant amount of time using their smartphones for emotion regulation, in particular to cope with unpleasant feelings such as boredom and stress. They report that smartphone-mediated emotion regulation is effective for attaining desired affective states. However, the perceived emotional benefits of smartphone emotion regulation do not emerge in lagged analyses predicting changes in momentary mood across a few hours, suggesting that emotional benefits may be transient or may reflect self-report biases. Participants discuss their perceptions of smartphone-supported emotion regulation in relation to smartphone addiction. This study provides evidence on how people use their smartphones for emotion regulation, and contributes to better understanding the complex relationship between smartphone use and emotional wellbeing.